(untitled) (Journal of Surgical Sciences, 2019)
Surgical drains are commonly placed in abdominal cavity to assess abdominal fluid or bloodcollections following major abdominal surgery. Whatever the purpose of drain placementeither therapeutic or prophylactic it must deserve a great caution while penetrating throughthe parietal wall. This case report documents one patient with serious iatrogenic complicationaroused from abdominal drain tube following an open total abdominal hysterectomy procedure. Journal of Surgical Sciences (2017) Vol. 21 (1) :42-44